Modern‐Day Nationwide Utilization of Intravascular Ultrasound and Its Impact on the Outcomes of Percutaneous Coronary Intervention With Coronary Atherectomy in the United States. (4th January 2019) - Desai, Rupak; Patel, Upenkumar; Fong, Hee Kong; Sadolikar, Ashish; Zalavadia, Dipen; Gupta, Sonu; Doshi, Rajkumar; Sachdeva, Rajesh; Kumar, Gautam
Abstract : Objectives: Intravascular ultrasonography (IVUS) and coronary atherectomy (CA) are useful modalities in managing calcified coronary lesions. Considering an inadequacy of data, we aimed to compare the outcomes with versus without IVUS assistance in percutaneous coronary interventions (PCIs) with CA. Methods: From the National (Nationwide) Inpatient Sample data set for the years 2012 to 2014, we identified adult patients undergoing PCI and CA with or without IVUS assistance using International Classification of Diseases, Ninth Revision, Clinical Modification codes. We assessed the impact of IVUS on procedural outcomes, length of stay, total hospital charges, and predictors of IVUS utilization by multivariable analyses. Discharge weights were used to calculate national estimates. Results: A total of 46, 095 PCIs with CA procedures were performed from 2012 to 2014, of these, 4800 (10.4%) procedures were IVUS‐assisted. IVUS‐assisted procedures showed lower odds of in‐hospital mortality (odds ratio, 0.57; P = .024) but higher odds of any cardiac complication (odds ratio, 1.25; P = .025). Total hospital charges were higher in IVUS‐assisted procedures without any substantial difference in the length of stay between the groups. Cardiac complication rates declined (from 16.2% to 14.8%) from 2012 to 2014, whereas inpatient mortality increased (1.1%–4.4%) in IVUS‐assisted procedures during the same period. The odds of IVUS utilization were higher in Asian/Pacific Islander and urban teaching and western region hospitals. Comorbidities, including hypertension, obesity, and chronic pulmonary disease, raised odds of IVUS utilization. Conclusions: IVUS‐assisted procedures showed lower in‐hospital mortality and higher iatrogenic and overall cardiac complications. The mortality rate in patients undergoing IVUS‐assisted PCI with CA was on the rise, with declining cardiac complication rates from 2012 to 2014.